UPAYA PENINGKATAN BRANDING DESA BEJI SEBAGAI KAMPUNG MINA UNTUK MENINGKATKAN PEMASARAN - Diah Titi Nawang Yudi; Ellen Prima (LPPM STAIMAS WONOGIRI, 2021)
As a country with abundant natural wealth, this should be an added point for Indonesia. Because the existing resources are used properly, they can be of economic value and of course will also help increase income. But in fact, this has not been running optimally, it can be seen from there are still quite a lot of underdeveloped areas and low regional income. The government has tried to deal with this by supplying funds for the development of each region. However, until now there are still many areas or villages that have not developed their potential properly. Beji village is one of the villages that has great potential in agriculture, this village is already known as the mina village and the largest supplier of fish cultivation in Banyumas. Broadly speaking, various natural resources and human resources are adequate, but there are still shortcomings in terms of media-based marketing, whereas nowadays media-based marketing has good prospects. This can be seen from the findings in the field where fish farmers still conventionally market their products or only from one person to another. So it's not surprising that the majority of customers who come are mostly those who are used to coming to Beji village, especially the fish market. Conventional systems like that of course are no longer effective if used in the digital age like now. For this reason, this service aims to increase the branding of Beji Village as Mina Village to the outside community by using the use of media. The use of media here was chosen to strengthen and expand the branding of Beji Village. The method used in this service is based on PAR (Participatory Action Research) to increase the branding of Beji Village as a Mina village. The service process was carried out by analyzing various problems of fish farmers related to efforts to improve branding, it was found that most of the existing fish farmers did not understand marketing methods using social media. Efforts made to deal with this were the creation of a marketing video containing an overview of the condition of fisheries in Beji Village, which was promoted through social media such as Instagram, Whatsapp, Facebook, and also youtube. The form of service is in the form of analyzing various problems faced and trying to find a way out, especially in this case, things that support media-based marketing.